If he were Toltec: Cesar Moro and the Mexican intellectual networks in the 1940s - Hadatty Mora, Yanna (2017)
This article aims to connect Moro to the Mexican cultural sphere, placing special emphasis on his link with different aesthetic and political groups during his so-called "Mexican period" (1938-1948). It mainly covers his connection with the exiles in Mexico, before and after the breakdown with the surrealist movement. At the same time, it presents a poem analysis which receives little attention, "Sueño de un dependiente de barbería a las tres de la tarde". ('Dream of a barber shop’s dependent at three in the afternoon'). This poem is considered to belong to this period, and not to the previous years before Mexico. This paper also analyses the meaning of the Toltec culture in cultural terms of the epoch, i.e., for the Mexican intelligentsia of the 1940s. It proposes the importance of reading Moro under these perspective.